An experiment on the impact of TRIZ-inspired thinking on solving insight problems - Laue, Ralf; Danek, Amory H. (Towards AI-aided invention and innovation, 2023)
Insight problems (problems requiring to restructure the mental representation of the problem in order to find a solution) are notoriously difficult to solve. Previous studies have used mostly problem-specific hints to improve problem solving performance. However, ideally a more general sort of training could be developed in order to increase solution rates. The present study tested whether a short intervention could be effective in facilitating problem solving performance for a battery of different problems. Specifically, it addressed the question whether referring to generic TRIZ concepts instead of problem-specific hints could support the problem solving process.
Gesehen am 02.12.2024